Effective Reduction in Nuclear DNA Contamination Allows Sensitive Mitochondrial DNA Methylation Determination by LC-MS/MS - Liang, Lin; González Molina, Luis Alfonso; Jellema, Pytrick G.; van Faassen, Martijn; Otten, Laura T. A.; Mennega, Kevin P.; Hof, Ingrid H.; Dijck-Brouwer, D. A. Janneke; Dolga, Amalia M.; Rots, Marianne G.; Niezen-Koning, Klary E. (International journal of molecular sciences, 2025)
Mitochondria are essential organelles for cellular energy production, playing a central role in driving metabolic processes and supporting critical intracellular functions. Neurometabolic disorders encompass a wide variety of conditions characterized by mitochondrial dysfunction. Owing to their bacterial ancestry, mitochondria possess an independent genome consisting of a circular DNA molecule (mtDNA), which has been reported to be subject to methylation. However, the technical challenges in the detection of mtDNA methylation have led to debates on its existence. One of the concerns is that the compactness of mtDNA can lead to suboptimal bisulfite conversion, thereby causing mtDNA methylation overestimation. To address this, liquid chromatography tandem mass spectrometry (LC-MS/MS) offers a bisulfite-independent readout; however, this method requires mtDNA samples devoid of nuclear DNA (nDNA) contamination. To diminish nDNA contamination, we isolated mtDNA from the TRIzol RNA phase. Importantly, pyrosequencing showed no significant difference in the methylation levels of mtDNA isolated from the TRIzol RNA phase compared to those from the TRIzol DNA phase, or isolated via total genomic DNA (gDNA). Across different human cell lines, LC-MS/MS detected significantly lower global methylation levels for DNA isolated from the TRIzol RNA phase than those from the TRIzol DNA or gDNA isolation. Moreover, using mtDNA isolated from the TRIzol RNA phase, LC-MS/MS validated the enhanced mtDNA methylation in HepG2 transgenic cell lines expressing mitochondrial-targeted DNA methyltransferases (means of 2.89% and 2.03% for MCviPI and MSssI transgenic cell lines, respectively), compared to two negative control cell lines (1.36 and 1.39%). When applying it to clinically relevant material, LC-MS/MS demonstrated a significantly lower global methylation level for platelet DNA isolated from the TRIzol RNA phase (mean of 1.98%) compared to gDNA isolations (mean of 4.32%). Similar findings were confirmed in mouse brain tissue, in which a significantly lower methylation level was detected in DNA isolated from the TRIzol RNA phase (1.79%) compared to that from gDNA isolation (5.12%). In conclusion, isolating mtDNA from the TRIzol RNA phase holds significant potential in future studies, particularly for the quantification of mtDNA global methylation by LC-MS/MS, a technique that is independent of bisulfite conversion and bioinformatic analysis.